Pengelolaan Prioritas Belanja Desa Pada Dana Desa Kota Raden Hulu Kabupaten Hulu Sungai Utara - Sari, Novita; Saipudin, Saipudin (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to (1) select the criteria for prioritizing village funds in Hulu Regency Sungai Utara, Hulu Raden City. (2) Know the priority of village spending for village development in Raden City Hulu, Hulu Regency Sungai Utara. The respondents to this study were 10 participants who were found to be effective in determining the village expenditures of the urban village of Raden Hulu used in the data processing using secondary analysis. Step. The results of this study show that alternative criteria for RPJMD, Village Capacity, and Village Issues influence village spending priorities according to preferences of 54% of village jobs, 30 % of RPJMD, and 16% of village capacity. According to the alternative criteria, the priority of village expenditure is village development at 42%, village enhancement at 32%, community development at 18%, and village management at 8%. It is concluded that rural development dominates 42%.